BUDAYA KERJA DI SEKOLAH BERBASIS ISLAM - Lupika Damai Riski; Burhanuddin Burhanuddin; Ahmad Yusuf Sobri (Universitas Negeri Malang, 2018)
Abstract: The purpose of the research was to describe working culture at Madrasah Tsanawiyah Assyafiiyah Gondang, district of Tulungagung. This study uses a qualitative approach and uses a type of case study research. The results of the study show that there is a varied work culture in MTs Assyafiiyah Gondang, district of Tulungagung, the work cultures are a culture of shaking hands between teacher and students, teacher and employee istighosah, students' guardianship, guardian culture, culture of integrity, responsibility, innovation , professional, and exemplary. In the implementation of the work culture in the madrasa there are also obstacles namely lack of time, there are teachers who are less enthusiastic in teaching, and lack of sustainability in dress. The solution that is done in overcoming these obstacles is the holding of deliberations, motivations and oral and written warnings..Keywords: culture, working culture Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan budaya kerja di Madrasah Tsanawiyah Assyafiiyah Gondang, Kabupaten Tulungagung. Penelitian ini menggunakan pendekatan kualitatif dan menggunakan jenis penelitian studi kasus. Hasil penelitian menunjukkan bahwa ada budaya kerja yang bervariasi di MTs Assyafiiyah Gondang, kabupaten Tulungagung, budaya kerja adalah budaya berjabat tangan antara guru dan siswa, guru dan karyawan istighosah, perwalian siswa, budaya wali, budaya integritas, tanggung jawab, inovasi, profesional, dan patut dicontoh. Dalam pelaksanaan budaya kerja di madrasah juga ada kendala yaitu kurangnya waktu, ada guru yang kurang antusias dalam mengajar, dan kurangnya keberlanjutan dalam berpakaian. Solusi yang dilakukan dalam mengatasi kendala ini adalah mengadakan rapat dan musyawarah, motivasi dan peringatan lisan dan tertulis.Kata Kunci: budaya, budaya kerja